2024
DOI: 10.56578/jimd030104
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing ComprehensiveWaste Management in Transition Economies Through Green Logistics: A Case Study of Bosnia and Herzegovina

Boris Novarlić,
Predrag Ðurić

Abstract: This study aims to elucidate the role of established public utility logistics in facilitating the integration of transition economies into the modern, developed world, with a particular focus on comprehensive waste management and the implementation of green logistics schemes. The research highlights the "green islands" waste collection system-networks of collection points that serve as separators for secondary raw materials from generated waste. It is demonstrated that such systems not only contribute to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…These multi-objective functions will be used in reinforcement learning to address the problem [38]. Furthermore, the study aiming to ensure sustainable management of resources and contribute to environmental protection and public health through the implementation of green logistics systems is actively underway [39]. Therefore, future studies also aim to explore optimizing the network of waste collection vehicles in urban areas or optimizing systems that bundle delivery tasks to adjacent destinations for execution.…”
Section: Discussionmentioning
confidence: 99%
“…These multi-objective functions will be used in reinforcement learning to address the problem [38]. Furthermore, the study aiming to ensure sustainable management of resources and contribute to environmental protection and public health through the implementation of green logistics systems is actively underway [39]. Therefore, future studies also aim to explore optimizing the network of waste collection vehicles in urban areas or optimizing systems that bundle delivery tasks to adjacent destinations for execution.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, special emphasis needs to be placed on factors that can be predicted (geological) compared to those that cannot be predicted (e.g., natural hazards) (Huang & Fan, 2016). According to numerous studies carried out worldwide, it is concluded that the developed countries of the world possess waste incinerators, where waste is treated in an environmentally defined manner, compared to transitional countries that mostly lack waste incinerators or have a negligible number of them and simply dispose of waste using basic landfill methods, which pollutes the environment and represents a potentially serious long-term health problem for residents (Keppert et al, 2012;Novarlić & Ðurić, 2024;Xiang et al, 2020;Zhao, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%